Rapid, Concurrent Formation of Organic Sulfur and Iron Sulfides During Experimental Sulfurization of Sinking Marine Particles. Issue 9 (21st September 2021) - Raven, M. R.; Keil, R. G.; Webb, S. M.
Abstract: Organic matter (OM) sulfurization can enhance the preservation and sequestration of carbon in anoxic sediments, and it has been observed in sinking marine particles from marine O2 ‐deficient zones. The magnitude of this effect on carbon burial remains unclear, however, because the transformations that occur when sinking particles encounter sulfidic conditions remain undescribed. Here, we briefly expose sinking marine particles from the eastern tropical North Pacific O2 ‐deficient zone to environmentally relevant sulfidic conditions (20°C, 0.5 mM [poly]sulfide, 2 days) and then characterize the resulting solid‐phase organic and inorganic products in detail. During these experiments, the abundance of organic sulfur in both hydrolyzable and hydrolysis‐resistant solids roughly triples, indicating extensive OM sulfurization. Lipids also sulfurize on this time scale, albeit less extensively. In all three pools, OM sulfurization produces organic monosulfides, thiols, and disulfides. Hydrolyzable sulfurization products appear within ≤200‐μm regions of relatively homogeneous composition that are suggestive of sulfurized extracellular polymeric substances (EPS). Concurrently, reactions with particulate iron oxyhydroxides generate low and fairly uniform concentrations of iron sulfide (FeS) within these same EPS‐like materials. Iron oxyhydroxides were not fully consumed during the experiment, which demonstrates that organic materials can be competitive with reactive iron for sulfide. These experiments support the hypothesis that sinking, OM‐rich and EPS‐rich particles in a sulfidic water mass can sulfurize within days, potentially contributing to enhanced sedimentary carbon sequestration. Additionally, sulfur‐isotope and chemical records of organic S and iron sulfides in sediments have the potential to incorporate signals from water column processes. Plain Language Summary: Vast amounts of organic carbon are stored in sediments on the ocean floor. This organic carbon is potentially food for organisms, and yet, under specific environmental conditions, it can escape being eaten and instead persist in sediments and rocks for millions of years. Here, we conduct experiments that test how the organic and inorganic materials in sinking marine particles can be transformed by 2 days of exposure to sulfidic environmental conditions, which are often associated with high rates of organic carbon burial in sediments. We find that these sulfidic conditions substantial alter the chemistry of ("pickle") particle organic materials, yielding products that resemble preserved organic materials in ancient deposits. Marine particles that encounter sulfidic conditions in the environment are therefore more likely to be preserved and buried in sediments, sequestering carbon out of the ocean and atmosphere. This process, called "sulfurization, " may act as a stabilizing feedback in the carbon cycle as ocean anoxic zones expand in response to ongoing climate change. Key Points: Organic matter in sinking marine particles sulfurizes rapidly in the presence of polysulfides, tripling its S:C ratio in 48 hr Iron monosulfides form from iron oxyhydroxide particles on the same time scale as organic sulfur Organic matter sulfurization in sinking particles may increase carbon burial in sediments, impacting sedimentary records and climate